Hambatan Kiprah Wanita di Dunia Information Technology dan Wanita di Malaysia Menjawab Tantangan ini - Ratnasari, Ade (JISKA (Jurnal Informatika Sunan Kalijaga), 2017)
Information and Technology sector grows quickly and there are few number of women than men in this field in big country such as US and UK. Women face many barriers to have equal access in this workforce. In this paper will analyse the barriers generally. This research use literature study to explore many facts in different countries. The different condition was happened in Malaysia. There, women succeed to minimize the barriers and they can optimize their participation in Information Teechnology workforce. This research can recommend the approach to increase more women in Inforrmation Technology field.